What is the Prevalence of Clinically Significant Endoscopic Findings in Subjects With Dyspepsia? Updated Systematic Review and Meta-analysis - Nasseri-Moghaddam, Siavosh; Mousavian, Amir-Hossein; Kasaeian, Amir; Kanno, Takeshi; Yuan, Yuhong; Ford, Alexander C.; Moayyedi, Paul (Clinical gastroenterology and hepatology, 2023)
The prevalence of clinically significant endoscopic findings in people with dyspepsia and understanding how symptoms can predict endoscopic pathology can help inform dyspepsia guidelines. We evaluated this in an updated systematic review and meta-analysis. We searched MEDLINE, EMBASE, Cochrane CENTRAL, and the Cochrane Database of Systematic Reviews from 2010 through to January 2022 to identify relevant articles. Eligible studies enrolled adults from the community, workplace, blood donation or screening clinics, family physician offices, or internal medicine clinics. Studies were required to report prevalence of dyspepsia and perform esophagogastroduodenoscopy (EGD). Prevalence of clinically significant endoscopic findings in subjects with and without dyspepsia was pooled for all studies and compared using odds ratios and 95% confidence intervals (CIs). The data were pooled with those of the 9 studies included in the prior review. Of 511 papers evaluated, 184 reported prevalence of dyspepsia. Fifteen reported prevalence of endoscopic findings among 41,763 participants (40.4% with dyspepsia). Erosive esophagitis was the most common abnormality (pooled prevalence, 11.0%; 95% CI, 8.9%–13.2%) followed by peptic ulcer (pooled prevalence, 4.4%; 95% CI, 2.5%–6.7%). The only finding encountered more frequently in individuals with dyspepsia, compared with those without, was peptic ulcer (odds ratio, 1.61; 95% CI, 1.08–2.39). More than 85% of EGDs were completely normal. Gastroesophageal cancer was rare (<0.4%) and equally prevalent among those with and without dyspepsia. Erosive esophagitis was the most common clinically significant finding at EGD, whereas gastroesophageal cancers were rare. Most pathology, including esophagitis and cancer, were found in similar proportions in both groups. These findings support noninvasive approaches to managing dyspepsia in the community, with EGD reserved for those at high risk of malignancy.